Cargo Quantification of Functionalized DNA Origami for Therapeutic Application - Young, Olivia J.; Dembele, Hawa; Rajwar, Anjali; Kwon, Ick Chan; Ryu, Ju Hee; Shih, William M.; Zeng, Yang C. (WILEY-V C H VERLAG GMBH, 2025)
In recent years, notable advances in nanotechnology-based drug delivery have emerged. A particularly promising platform in this field is DNA origami-based nanoparticles, which offer highly programmable surfaces, providing precise control over the nanoscale spacing and stoichiometry of various cargo. These versatile particles are finding diverse applications ranging from basic molecular biology to diagnostics and therapeutics. This growing interest creates the need for effective methods to quantify cargo on DNA origami nanoparticles. The study consolidates several previously validated methods focusing on gel-based and fluorescence-based techniques, including multiplexed quantification of protein, peptide, and nucleic acid cargo on these nanoparticles. In this work, how gel band intensity and nanodrop fluorescence readings can be used to quantify protein, peptide, and RNA cargo on a DNA origami nanoparticle is demonstrated. This work may serve as a valuable resource for groups of researchers keen on utilizing DNA origami-based nanoparticles in therapeutic applications.